The Relationship between Self-Confidence and Student Learning Achievement in Schools A systematic Literature Review - Nur Sakinah Hsb; Riski Hariani Hsb; Riski Fadilah Daulay; Rominta Pasaribu; Nurhayati Siregar (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Learning achievement is one of the main indicators of educational success and is influenced by various internal and external factors. One important internal factor is self-confidence, which affects students' courage, motivation, participation, and ability to complete academic tasks effectively. This study aims to analyze the influence of self-confidence on students' learning achievement based on findings from previous studies. The research employed a library research method using a descriptive qualitative approach. Data were collected from relevant scientific sources, including national and international journal articles, books, conference proceedings, and other scholarly publications issued between 2019 and 2025. The collected data were analyzed using content analysis, involving data reduction, data presentation, synthesis, and conclusion drawing. The findings indicate that self-confidence has a positive influence on students' learning achievement. Students with higher levels of self-confidence tend to participate more actively in classroom activities, express their opinions confidently, demonstrate stronger learning motivation, and complete academic tasks independently, resulting in better academic performance. Therefore, fostering students' self-confidence should become an important concern for teachers and schools as an effective strategy to improve learning quality and academic achievement.